A generic instantaneous undeformed chip thickness model for the cutting force modeling in micromilling. (June 2016) - Li, Kexuan; Zhu, Kunpeng; Mei, Tao
Abstract: The precise modeling of the instantaneous undeformed chip thickness is one of the key issues in the mechanics of micromilling. While most current models noticed the influences of the tool tip trochoidal trajectory and tool runout, they took account only the workpiece removed by immediate passing tooth but not more preceded teeth. These lead to inaccuracy when the single edge cutting occurred, which has been identified to be a prevalent phenomenon in micromilling operation. In this paper, the actual cutting area in micromilling is derived, and then a generic instantaneous undeformed chip thickness model is proposed by considering the cutting trajectory of all passing teeth in one cycle. Additionally, this study derives a criterion that could determine the single-edge-cutting phenomenon in multi-tooth micromilling from the geometric relations. The accuracy of the model is verified by the real experimental data and the result are shown superior to known models. Highlights: Introduced a generic instantaneous undeformed chip thickness model in micromilling. Derived a function that determine the single-edge-cutting phenomenon. Showed good generalizations to the existed models. Showed better accuracy compared to previous celebrated model.